EFFECT OF FUSION REACTION PRODUCTS HEATING ON THE VOLUME IGNITION OF DT AND D3He FUEL PELLETS (Journal of Sciences, Islamic Republic of Iran)
Laser fusion simulations are carried out for DT and D- He pellets by using a hydrodynamic code including heating from all charged reaction products and neutrons. It is shown that the inclusion of the side reactions and heating from all reaction products in the fuel pellets have an appreciable effect on the plasma temperature, the ICF drive energy requirement, fusion gain and the ignition conditions. The total input energy is decreased and the burn efficiency and total gain are increased compared to the results of simple volume ignition calculations